2015
DOI: 10.7705/biomedica.v36i0.2990
|View full text |Cite
|
Sign up to set email alerts
|

Análisis filogenético del virus del chikungunya en Colombia: evidencia de selección purificadora en el gen E1

Abstract: Contribución de los autores:Katherine Laiton-Donato y José A. Usme-Ciro: concepción y diseño del estudio Todos los autores participaron en el análisis y la interpretación de los resultados, la revisión crítica del manuscrito, la aprobación de la versión final y de todos los aspectos del manuscrito. Objetivo. Identificar el genotipo o los genotipos responsables de la primera epidemia por el virus del chikungunya en Colombia y la variabilidad genética asociada a su dispersión en el territorio nacional. Materiale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…Finally, genotype III was found in the DENV-3 strains, which has been the predominant genotype in Colombia since its introduction in 2002 [ 60 ]. In the case of the samples positive for CHIKV, sequencing revealed the presence of the Asian strain, the same strain that has been previously reported in Colombia [ 18 , 61 , 62 ]. Finally, although no sequencing of the samples positive for ZIKV was performed because the real-time PCR primers amplify a specific region of the Asian/Caribbean strain [ 31 ], we can presume that these samples belong to this lineage, which is the same that has been previously reported in the country [ 62 64 ].…”
Section: Discussionsupporting
confidence: 70%
“…Finally, genotype III was found in the DENV-3 strains, which has been the predominant genotype in Colombia since its introduction in 2002 [ 60 ]. In the case of the samples positive for CHIKV, sequencing revealed the presence of the Asian strain, the same strain that has been previously reported in Colombia [ 18 , 61 , 62 ]. Finally, although no sequencing of the samples positive for ZIKV was performed because the real-time PCR primers amplify a specific region of the Asian/Caribbean strain [ 31 ], we can presume that these samples belong to this lineage, which is the same that has been previously reported in the country [ 62 64 ].…”
Section: Discussionsupporting
confidence: 70%
“…Specific CHIKV genotypes were not identified in this study. However, Laiton-Donato et al identified the genotypes responsible for the CHIKV epidemic in Colombia during 2014–2015 and found only the Asian genotype ( 21 ). We ruled out dengue virus infection by measuring blood for specific antibodies and nonstructural protein 1 antigen with the commercial SD BIOLINE Dengue Duo kit (Standard Diagnostic, Inc., Yongin, South Korea).…”
Section: Methodsmentioning
confidence: 99%
“…In recent decades, Colombia has suffered epidemics due to a large number of emerging arboviruses such as dengue virus, Venezuelan equine encephalitis virus, CHIKV, and Zika, which have caused severe public health problems 13 . The first case of local transmission of CHIKV in Colombia was notified in August 2014 in the department of Bolivar 14 . According to the Pan American Health Organization, Colombia was the country with the third highest number of cases after Brazil and the Dominican Republic 15 ; between 2014 and 2015 there were 460,484 cases diagnosed by clinical symptoms and 4,658 confirmed by the laboratory 16,17 .…”
Section: Introductionmentioning
confidence: 99%